Reducing body fat with altitude hypoxia training in swimmers: role of blood perfusion to skeletal muscles - Chia, Michael; Liao, Chin-An; Huang, Chih-Yang; Lee, Wen-Chih; Hou, Chien-Wen; Yu, Szu-Hsien; Harris, M Brennan; Hsu, Tung-Shiung; Lee, Shin-Da; Kuo, Chia-Hua (Chinese journal of physiology, 2013)
Swimmers tend to have greater body fat than athletes from other sports. The purpose of the study was to examine changes in body composition after altitude hypoxia exposure and the role of blood distribution to the skeletal muscle in swimmers. With a constant training volume of 12.3 km/day, young male swimmers (N = 10, 14.8 ± 0.5 years) moved from sea-level to a higher altitude of 2,300 meters. Body composition was measured before and after translocation to altitude using dual-energy X-ray absorptiometry (DXA) along with 8 control male subjects who resided at sea level for the same period of time. To determine the effects of hypoxia on muscle blood perfusion, total hemoglobin concentration (THC) was traced by near-infrared spectroscopy (NIRS) in the triceps and quadriceps muscles under glucose-ingested and insulin-secreted conditions during hypoxia exposure (16% O2) after training. While no change in body composition was found in the control group, subjects who trained at altitude had unequivocally decreased fat mass (-1.7 ± 0.3 kg, -11.4%) with increased lean mass (+0.8 ± 0.2 kg, +1.5%). Arterial oxygen saturation significantly decreased with increased plasma lactate during hypoxia recovery mimicking 2,300 meters at altitude (~93% versus ~97%). Intriguingly, hypoxia resulted in elevated muscle THC, and sympathetic nervous activities occurred in parallel with greater-percent oxygen saturation in both muscle groups. In conclusion, the present study provides evidence that increased blood distribution to the skeletal muscle under postprandial condition may contribute to the reciprocally increased muscle mass and decreased body mass after a 3-week altitude exposure in swimmers.